Pengaruh Substitusi Tepung Koro Pedang (Canavalia Ensiformis L) Terhadap Tingkat Pengembangan DanDaya Terima Donat - NUR AINI, LATIFAH; , Fitriana Mustikaningrum, S.Gz., M.Sc; , Pramudya Kurnia, S.TP., M.Agr (2016)
Koro pedang (Canavalia Ensiformis L) can be processed into the powder that can be used as a substitution of flour. Koro Pedang can be used as the main ingredient of meal including cakes, cookies, brownies, tempeh, and it is also potentially processed into a donut. Koro Pedang has adequate nutrition including 60,1% carbohydrate, 30,36% protein, and 8,3% fiber (Sudiyono,2010). The purpose of the studies is to know the development and the receptions of Koro Pedang (Canavaliaensiformis L) as the substitution of established flour as the main ingredient to make a donut. This research uses experimental method with random design with 3 treatments (2,5%, 5%, dan 7,5%). The analysis of developmental level and its acceptance uses One Way Anova test with the 95% significant rate and if it has effect it will be continued with the Duncan Multiple Range Test (DMRT). The research shows that there is no substitution effect of Koro Pedang powder on the developmental level and the reception of donut. Donuts with the 2.5 substitution are most preferred by panelists. The research concludes that here was no substitution effect of Koro Pedang Powder on the process of making donuts on the development and the reception of donuts. Thus the research suggests that to make a donut form Koro Pedang powder uses the 2.5% substitution Suggestion: Making donuts sword koro suggested the substitution of 2.5%